Influência da reflexão estruturada na acurácia diagnóstica de estudantes de odontologia para casos de lesões bucais - Baldim, Arislaine Andrade (2020)
Dentistry students need to constantly diagnose oral lesions of different complexities. Since the first periods of the undergraduate program, there is a need to develop and improve clinical reasoning. The use of structured reflection to increase diagnostic accuracy has gained prominence as an instructional strategy and its effect in dentistry has not been documented. Objective: to evaluate the effect of structured reflection on the diagnostic accuracy of dentistry students for the resolution of clinical cases of oral lesions. Methods: an experimental study with dentistry students was carried out in two phases (training and evaluation phases). Students from the seventh and eighth emester of the dentistry program at UNIFENAS, Alfenas campus, were enrolled. They were divided into two groups: control (CG) and reflection (RG). In the training phase, both groups resolved 12 clinical cases of oral lesions. The CG pointed out the most likely diagnosis and later performed a distracting activity. The RG pointed out the diagnosis and carried out a structured reflection. In the evaluation phase, after 7 days, the two groups freely resolved another 12 clinical cases of oral lesions, alike those in the training phase. In both phases, there were six easy and six difficult ones. Results: 52 students participated in the study: 21 in the CG and 31 in the RG. The groups were similar in terms of sex and age. The CG had significantly higher prior academic performance than the RG. The diagnostic accuracy for all cases and for difficult ones was low. There was no difference in diagnostic accuracy between the two groups in any of the study phases. A significant improvement in accuracy was observed in the CG, when Phase 2 was compared with Phase 1, both for all cases (p=0.017) and for difficult ones (p=0.046). In the RG there was an improvement in performance in Phase 2, but the p value was borderline (p=0.051). Conclusion: in this study, the structured reflection did not increase the diagnostic accuracy for oral lesions among dentistry students in the seventh and eighth semesters.